A Multicenter International Randomized Controlled Manikin Study on Different Protocols of Cardiopulmonary Resuscitation for Laypeople: The MANI-CPR Trial. Issue 4 (August 2021) - Baldi, Enrico; Contri, Enrico; Burkart, Roman; Borrelli, Paola; Ferraro, Ottavia Eleonora; Paglino, Martina; Pugliesi, Marinella; Barbati, Chiara; Bertaia, Daniele; Tami, Christian; Lopez, Daniel; Boldarin, Susi; et al.
Abstract : Background: Compression-only cardiopulmonary resuscitation (CPR) is a suggested technique for laypeople facing out-of-hospital cardiac arrest (OHCA). However, it is difficult performing high-quality CPR until emergency medical services arrival with this technique. We aimed to verify whether incorporating intentional interruptions of different frequency and duration increases laypeople's CPR quality during an 8-minute scenario compared with compression-only CPR. Methods: We performed a multicenter randomized manikin study selecting participants from 2154 consecutive laypeople who followed a basic life support/automatic external defibrillation course. People who achieved high-quality CPR in 1-minute test on a computerized manikin were asked to participate. Five hundred seventy-six were enrolled, and 59 were later excluded for technical reasons or incorrect test recording. Participants were randomized in an 8-minute OHCA scenario using 3 CPR protocols (30 compressions and 2-second pause, 30c2s; 50 compressions and 5-second pause, 50c5s; 100 compressions and 10-second pause, 100c10s) or compression-only technique. The main outcome was the percentage of chest compressions with adequate depth. Results: Five hundred seventeen participants were evaluated. There was a statistically significant difference regarding the percentage of compressions with correct depth among the groups (30c2s, 96%; 50c5s, 96%; 100c10s, 92%; compression only, 79%; P = 0.006). Post hoc comparison showed a significant difference for 30c2s ( P = 0.023) and for 50c5s ( P = 0.003) versus compression only. Regarding secondary outcome, there were a higher chest compression fraction in the compression-only group and a higher rate of pauses longer than 10 seconds in the 100c10s. Conclusions: In a simulated OHCA, 30c2s and 50c5s protocols were characterized by a higher rate of chest compressions with correct depth than compression only. This could have practical consequences in laypeople CPR training and recommendations. Clinical Trial Registration: NCT02632500 Abstract : Supplemental digital content is available in the text.